PENGALIHAN PENYELENGGARAAN URUSAN PEMERINTAHAN BIDANG PERTAMBANGAN BATUAN (GALIAN C) DARI PEMERINTAH KABUPATEN KAMPAR KE PEMERINTAH PROVINSI RIAU TAHUN 2017-2018 - Reza "; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
After the enactment of Law no. 23/2014 The Government of Kampar Regency handed over the authority to manage mining affairs (Batuan Galian C) to the Riau Provincial Government. The management of mining affairs in Kampar Regency is technically managed by the Branch Office of Energy and Mineral Resources of Riau Province, region I of Kampar Regency after the transfer of authority. The purpose of this study was to analyze and describe the processes and policies after the transfer of authority for mining affairs from the Regency / City Government to the Riau Provincial Government which was carried out in Kampar Regency.This study aims to examine how and what are the inhibiting factors for the diversion of the administration of quarry (C) mining affairs in the Kampar Regency Government in 2017-2018. This research is a descriptive study with a qualitative approach. The location of this research was conducted in Kampar Regency and Pekanbaru City. Data collection techniques used are through interviews and documentation. The data analysis technique used is an interactive analysis model.The results of the study concluded that based on the observations and analysis of the researchers were 1). The process of transferring government authority to mining affairs is proceeding quite well. However, especially in Kampar Regency, the Kampar Regency Mining Service Office Building looks abandoned and is not being used. Meanwhile, the Kampar District Office I Branch had to rent a building to become an office. 2). After the transfer of government affairs in the mining sector to the Riau Provincial Government, the Riau Provincial Government carried out many efforts to be able to properly exercise its authority based on the applicable Law. One of them is forming a Service Branch which is divided into 7 Regions. However, in the field it can be seen that the implementation of guidance and supervision carried out by the Riau Province government, both the Riau Province ESDM Service and the Kampar District I Regional Office Branch, has not been optimal. 3). Factors inhibiting the diversion of the implementation of quarry mining affairs c, namely: a) Lack of government coordination. b). Inadequate competency of personnel / employees. c). The number of employees is insufficient. d). The transfer of mining affairs to the Provincial Government is not accompanied by a transfer of mining business taxes / levies.   Keywords: Operational Transfer, Authority, Quarry Mining C